1989
DOI: 10.1038/jcbfm.1989.77
|View full text |Cite
|
Sign up to set email alerts
|

Local Cerebral Glucose Utilization in Chronic Middle Cerebral Artery Occlusion in the Cat

Abstract: Summary: This study examines the correlation between local CMRglc (LCMRglc) alterations and clinicopatholog ical changes in a chronic middle cerebral artery (MCA) occlusion model in the cat. The left MCA was occluded for a period of 2 h. The animals were grouped into mild, moderate, and severe ischemia based on the depression of the EEG 30 min after the MCA occlusion. Follow ing release of the clip, the animals were allowed to re cover for a week during which time daily neurological examinations were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…This study found that voxels showing low N-acetyl aspartate and high lactate were associated with histopathological sections containing macrophages (10). Other studies of focal CMRglc in an animal model of stroke have shown an increase in glucose metabolism that correlates highly with the histopathological finding of macrophage infiltration (16).…”
Section: Discussionsupporting
confidence: 52%
“…This study found that voxels showing low N-acetyl aspartate and high lactate were associated with histopathological sections containing macrophages (10). Other studies of focal CMRglc in an animal model of stroke have shown an increase in glucose metabolism that correlates highly with the histopathological finding of macrophage infiltration (16).…”
Section: Discussionsupporting
confidence: 52%
“…However, other possible reasons for increases in CMR g lc in postischemic brain tissue are also known. Recently, Komatsumoto et al (1989) dem onstrated an increase in CMR g lc caused by phago cytes 7 days after transient occlusion of the middle cerebral artery in the cat. Dietrich et al (1 986b ) have reported a hypermetabolic zone coincident with foci of intense macrophage infiltration 5 days after photochemically induced cortical infarction in the rat.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the arterial blood pressure, arterial blood gases (pH, PCO 2 , PO 2 and glucose in blood), and body temperature did not change during the chronic postischemic period in the four-vessel occlusion model in conscious rats [21,22]. Furthermore, arterial blood pressure and arterial blood gases showed no significant differences between the MCA-occluded group and the sham group during the measurement of cerebral glucose utilization at 7 days after MCA occlusion in the cat [23]. Thus, we assumed that the physiological parameters were unchanged during the measurement of LCBF and LCMR glc in this study.…”
Section: Discussionmentioning
confidence: 84%